Pengaruh Mata Pelajaran Akidah Akhlak Terhadap Kebiasaan Mengucap Salam Dan Berjabat Tangan Kepada Guru Oleh Siswa Kelas 4 MI Syafa’at Pesantren Tembelang Jombang - Waslah - (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2019)
Based on observations by researchers at MI Syafa’at Pesantren, there are still manystudents who are not used to saying greetings and shake hands with the teacherwhile at school. Based on this, the researcher wants to know how the influencebetween the theories that have been studied in the classroom is given by the teacherthrough the Akidah Akhlak subjects by applying the habit of greeting and shakinghands. Therefore the formulation of the problem in this study is how the influence ofmoral akidah subjects on the habit of greeting and shaking hands of students. Thisstudy aims to determine whether there is an effect of moral akidah lessons on thehabit of greeting and shaking hands by class 4 students MISyafa’atPesantrenTembelang Jombang. This study is a type of correlational researchendexpost facto with a quantitative approach. Correlational research is a study that isintended to determine whether there is a relationship between two or severalvariables. Expost facto said because in this study no treatment was made on the objectof research but only revealed the facts to the respondent. The researcher uses apopulation sample, all members of the population are used as a sample, namely allstudents in grade IV MI Syafa’at Pesantren25 students. The instrument in this studyused a questionnaire to retrieve data. The data analysis technique used in this studyis simple linear regression. Based on the analysis of the data and the results of theresearch and the hypothesis testing that has been done, the calculation resultsobtained obtained the value of Adjusted R Square is 0.599 which means that 59.9% ofthe habit of saying greetings and shaking hands can be influenced by moral aqlahsubjects. While the remaining 40.1% are influenced by other variables besides thestudents' moral akidah subjects. In addition, the Annova calculation obtained Fcountof 34.302>Ftable 4.26 with a significance level of 0.000 <0.05. Paired with theCoeffisients calculation, tcount = 9.819>ttable 1.710 with a significance value of 0.000<0.05. Thus it can be concluded that Ho is rejected and Ha is accepted. That is, there isa significant influence between moral akidah subjects to the habit of greeting andshaking hands of grade 4 students MI Syafa’at Pesantren.